Situation Report: Romania, 9 July 1982 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. And Odd Project fir the Development of Black Sea Energy Electricity and Heating Oil: Raising Rates and Cutting Consumption Ceausescu Visits Iraq and Jordan Selling Workers Their Own Property Babes-Bolyai in Cluj: A Tale of Two Universities Political Ballast Burdens Music Life Romania and the Israeli Invasion of Lebanon World Cup Soccer